Real-world evidence of tofacitinib effectiveness and safety in patients with refractory ulcerative colitis. Issue 3 (March 2020) - Lair-Mehiri, Loriane; Stefanescu, Carmen; Vaysse, Thibaut; Laharie, David; Roblin, Xavier; Rosa, Isabelle; Treton, Xavier; Abitbol, Vered; Amiot, Aurélien; Bouguen, Guillaume; Dib, Nina; Fumery, Mathurin; et al.
Abstract: Background: Phase III trials demonstrated effectiveness of tofacitinib, an oral Janus kinase inhibitor, to induce and maintain remission in patients with moderate-to-severe active ulcerative colitis (UC). Aims: We report the real-world effectiveness and safety of tofacitinib in patients with UC in France. Methods: From February 2017 to December 2018, we performed a national French cohort study, which included all consecutive patients with an active UC refractory to anti-TNF and vedolizumab, who received tofacitinib. Outcomes were survival without colectomy, survival without tofacitinib discontinuation and steroid-free clinical remission at weeks 14, 24 and 48. Results: Thirty-eight patients were included, with a median follow-up of 41.5 (18.5–56.8) weeks. Survival without colectomy was 77% [95% confidence interval (95%CI): 59.3–87.9] at week 24 and 70% (95%CI: 50.9–82.8) at week 48. Survival without treatment discontinuation was 70% (95%CI: 52.6–82.3) at week 24. Steroid-free clinical remission was observed in 13 (34%) patients at week 48. Adverse events occurred in 14 (37%) patients, including 6 severe adverse events and three herpes zoster infections. Conclusion: In a highly refractory UC population, one third of patients treated with tofacitinib achieved steroid-free clinical remission at week 14 and 70% of patients avoided colectomy at one year, with an acceptable safety profile. These data confirm tofacitinib effectiveness in UC, especially after multiple biologic failures.